Poetry's Total Scandal: Poets and Postmen in Antonio Skármeta's "El cartero de Neruda" - Gräbner, Cornelia (Tropelías: Review of Literary Theory and Comparative Literature, 2012)
The argument put forward here takes Antonio Skármeta's short novel El cartero de Neruda (Ardiente paciencia) as a theorization of the relationship between poetry and politics, by way of the concept-metaphors (Mieke Bal) that are deployed in the novel. Skármeta stages the public role of poetry through the telling of a story about the poet Pablo Neruda and his postman Mario Jiménez. The relationship between poetry and politics is analysed with reference to Hazard Adams' concept of «the offense of poetry» and Roland Barthes' reflections on the total scandal of language in his essay «Écrivains et écrivants» (1964), here adapted as «the total scandal of poetry». In contradistinction to Barthes, who argues that the total scandal of language is impossible because of the absorption of scandalous language by the literary institution, Skármeta's short novel suggests that the total scandal of poetry is indeed possible when, as in the case of Pablo Neruda, Mario Jiménez and Salvador Allende, poetry becomes a constitutive part of a political project, within which it functions as a reminder of dignity and as the touchstone for political integrity.Keywords: poetic offense, scandal of language, Pablo Neruda, Arthur Rimbaud, Roland Barthes, Antonio Skármeta. En este artículo examino la breve novela El cartero de Neruda (Ardiente paciencia) de Antonio Skármeta, como una teorización de la relación entre poesía y política, a través de los conceptos-metáfora (Mieke Bal) que el autor desarrolla en la novela. Skármeta evidencia el rol público de la poesía a través del relato de una historia sobre el poeta Pablo Neruda y su cartero Mario Jiménez. La relación entre poesía y política es analizada con referencia al concepto de «ofensa de la poesía» (Hazard Adams) y a las reflexiones de Roland Barthes sobre el «éscandalo total del lenguaje» («Écrivains et écrivants», 1964), aquí adaptado como «escándalo total de la poesía». Al contrario de Barthes, quien arguye que el escándalo total del lenguaje es imposible porque la institución literaria lo absorbe, la novela de Skármeta sugiere que el escándalo total de la poesía adquiere posibilidad de ser cuando la poesía —como en Pablo Neruda, Mario Jiménez y Salvador Allende— se convierte en elemento constitutivo de un proyecto político, dentro del cual funciona como recordatorio de la dignidad y como piedra de toque para la integridad política.Palabras clave: ofensa de la poesía, escándalo del lenguaje, Pablo Neruda, Arthur Rimbaud, Roland Barthes, Antonio Skármeta.